Alfa Mangostin Extract (Garcinia Mangostana L) Effectiveness on the Biofilm Thickness Growth of Streptococcus Sanguinis. - Rahmawati Sri Praptiningsih; Rosa Pratiwi; tazkia Yustisiani Nurafifah (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: Periodontal disease is caused by the accumulation of bacteria from biofilms in the periodontal tissues. Streptococcus sanguinis is one of bacteria lives in biofilm. One of the herbal ingredients that can be used as an antibacterial is the mangosteen fruit (Garcinia mangostana L.), especially the rind of the mangosteen fruit. The main compound in the mangosteen rind is known as alfa-mangostin, the compound alfa-mangostin has anti-bacterial benefits. The purpose of this research is to determine the effectiveness usage of alpha mangostin toward Streptococcus sanguinis biofilm thickness growth. Method: Experimental research design, with post-test only control group design with a sample size of 27. The treatment group consisted of alpha mangostin 3.125, 6.25, and 12.5 g/ml and the control group were distilled water. Measurement of Streptococcus sanguinis biofilm thickness was carried out by ELISA-reader. The statistical test was carried out using the One Way Anova test. Results: The results showed the lowest average thickness of Streptococcus sanguinis with the addition of -mangostin 12.5 g/ml was 0.371, while the thickness of Streptococcus sanguinis with the addition of chlorhexidine was the highest at 1.860. One Way Anova test obtained a significance number of 0.001 (p